Transforming Students' Paradigms Regarding Research through Experiential Learning in Entrepreneurial Accounting - Gde Deny Larasdiputra; Ni Putu Riski Martini (Journal of Governance, Taxation and Auditing, 2026)
This study aims to explore the shift in students' paradigms regarding research through an entrepreneurial accounting learning approach based on practical experience with an MSME. Students often perceive research or the undergraduate thesis as a rigid administrative obligation detached from real-world realities. Employing a qualitative approach with an explorative-reflective design, this study utilized "Poison Coffee Shop"an MSME as a "living laboratory" for accounting students over the course of one academic semester.Data collection involved semi-structured reflective interviews, limited participant observation, and students' written reflective journals, all of which were analyzed using thematic analysis. The findings indicate that students' direct engagement with the MSME's operational and managerial dynamics successfully deconstructed myths surrounding academic research. Students experienced a paradigm shift, coming to view the processes of investigation, financial data analysis, and reflection as essential life skills a form of "living research."This learning model not only bridges theory and practice but also contributes significantly to the achievement of SDG 4 (Quality Education) through reflective pedagogical innovation, and SDG 8 (Decent Work and Economic Growth) by fostering an analytical and sustainable entrepreneurial orientation.